Executive functions and the role of dieting: A comparison between English and Greek females - Eirini TATSI; Noreen CASWELL (Journal of Health and Social Sciences)
Introduction: This study investigated and compared the effect of dieting status and culture on executi- ve functions (EFs) between English and Greek females. The moderating role of restrained eating, preoc- cupying cognitions, depressed affect and IQ was also investigated to provide further evidence of the nature of this effect. Methods: A between-subjects design was employed, where 192 females were recruited from UK (n =45) and Greek (n =147) Universities; 99 were current dieters and 93 were non-dieters. The Behavior Rating In- ventory of Executive Function (BRIEF-A) was used to assess Executive Functions (EFs). Participants also completed the Dutch Eating Behaviour Questionnaire-Restraint (DEBQ-R), Preoccupying cognitions, Centre for Epidemiologic Studies Depression scale (CES-D), Raven's Advanced Progressive Matrices-Set I, and a questionnaire acquiring demographic information. MANOVA and MANCOVA analyses were carried out. Results: There was a significant multivariate main effect for dieting status (P < 0.05) and nationality (P < 0.001). Specifically, dieters self-report greater difficulty on inhibit (P < 0.001), self- and task-monitor, organisation of materials and working memory (P < 0.01), and shift, emotional control, initiate and plan/ organise (P < 0.05). A significant univariate effect was found for nationality, in terms of emotional control (P < .0.01), whereby a higher mean T-score was revealed for Greek (M = 62.12; SD = 11.01) compared to English females (M = 59.28; SD = 13.95). With DEBQ-R and preoccupying cognition scores entered as covariates, the effect of nationality, on emotional control, remained significant (P < 0.001). However, none of the main effects for dieting status remained significant (P > 0.05). Discussion and Conclusion: Greek females self-report greater difficulty in controlling their emotions. Dieters found to have a poorer ability on the components of EFs; nationality also found to have an effect on EFs. Outcomes of this research provide fruitful implications on the association between dieting, culture and EFs.